Redefining teacher mentoring: a methodological design proposal that pro-motes improved practices through pedagogical and curricular manage-ment - Rodriguez Becerra, Darlin (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This article proposes redefining teacher mentoring, positioning it as a strategic axis for driving the paradigm shift required for educational improvement. The research offers a critical view of the current model and challenges school leaders to cha-llenge their practices, considering the challenges of pedagogy for the 21st century and the systemic transformations facing teachers. The central question guiding the study is: Is the current teacher mentoring model sufficient to promote real impro-vements in pedagogical practices and curriculum management? Using a qualitative approach, the research was conducted in a technical-professional school, incorporating instruments validated by experts and applied to 36 teachers and 978 stu-dents. The methodological design is structured in progressive phases of diagnosis, intervention, and evaluation, allowing for a systematic analysis of pedagogical practices and guiding evidence-based decision-making (MINEDUC, 2023; Benavides & Manzano, 2019). The results show a significant appreciation of mentoring as a catalyst for improving planning, implementing active methodologies, and developing key competencies in students (Afzal, 2021; Darling-Hammond & Oakes, 2019).However, significant challenges also emerge regarding the collaborative work culture. A mentoring model is proposed that positions the Pedagogical Technical Unit as the coordinating core of training processes, promoting distributed leadership (Rincón-Gallardo, 2023), and redefining mentoring as a transformative strategy, going beyond traditional control and super-vision (Fullan & Hargreaves, 2021).
Keywords: Teacher mentoring; Methodological design; Pedagogical and curricular management